Electronic recycling plants: human resources and OHS management case studies. Issue 3 (9th March 2021) - Gravel, Sylvie; Côté, Daniel; Gladu, Stéphanie; Labrèche, France; Gravel, Sabrina; Bakhiyi, Bouchra; Zayed, Joseph
Abstract : Purpose: The electrical and electronic recycling industry is experiencing significant growth while paying no particular attention to the health and safety of recycling workers. Who are these recycling workers? How are they recruited and trained in OHS measures? This article will attempt to answer these questions. Design/methodology/approach: As part of a toxicological study carried out on five companies, samples were taken from employees ( n = 100) and their working environment. Among them, 26 workers and six managers also participated in interviews on the management of OHS preventive practices. This article presents analyses of the recruitment strategies for these workers and the management of preventive measures. Findings: The main findings were that preventive practices vary according to the company's social mission and recruitment strategy. OHS preventive practices vary among the companies, even though the workers are similarly exposed to multiple contaminants. Precarious employment relationships put these workers in a vulnerable position. Originality/value: Although recycling electrical and electronic equipment (e-recycling) has been an ecological and moral concern in Western societies for several decades, occupational health and safety (OHS) management in recycling plants has received little attention.